2022
DOI: 10.1002/cbic.202200071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nicotinamide Mononucleotide from Xylose via Coupling Engineered Escherichia coli and a Biocatalytic Cascade

Abstract: β‐Nicotinamide mononucleotide (NMN) has recently gained attention for a nutritional supplement because it is an intermediate in the biosynthesis of nicotinamide adenine dinucleotide (NAD+). In this study, we developed NMN synthesis by coupling two modules. The first module is to culture E. coli MG1655 ▵tktA ▵tktB ▵ptsG to metabolize xylose to generate D‐ribose in the medium. The supernatant containing D‐ribose was applied in the second module which is composed of EcRbsK‐EcPRPS‐CpNAMPT reaction to synthesize NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(128 reference statements)
4
10
0
Order By: Relevance
“…As expected, a further decrease in the NMN yield was observed (Figure S5b), indicating that PPi indeed has the inhibitory effects on NMN production. This result was well consistent with a recent study that suggested that PPi has feedback inhibition on Nampt (Ngivprom et al, 2022). Next, we tested whether the NMN production could be improved by removing the PPi inhibition.…”
Section: Testing and Optimizing Nmn Biosynthesissupporting
confidence: 91%
“…As expected, a further decrease in the NMN yield was observed (Figure S5b), indicating that PPi indeed has the inhibitory effects on NMN production. This result was well consistent with a recent study that suggested that PPi has feedback inhibition on Nampt (Ngivprom et al, 2022). Next, we tested whether the NMN production could be improved by removing the PPi inhibition.…”
Section: Testing and Optimizing Nmn Biosynthesissupporting
confidence: 91%
“…Consequently, we decided to use the enzymes with the tags, as this likely is the most pragmatic and straightforward preparation of the enzymes for their use in chemical synthesis. The assay setup used for all PPKs is similar to established ATP regeneration systems with PPK2 enzymes, with a 10:1 excess of polyP (calculated as single phosphates [49]) over the nucleotide (default concentration in this work 2 mM) [39,[50][51][52]. This is also a realistic scenario for biosynthetic reactions using PPKs for the production of NTPs [22,52].…”
Section: Resultsmentioning
confidence: 99%
“…The assay setup used for all PPKs is similar to established ATP regeneration systems with PPK2 enzymes, with a 10:1 excess of polyP (calculated as single phosphates [49]) over the nucleotide (default concentration in this work 2 mM) [39,[50][51][52]. This is also a realistic scenario for biosynthetic reactions using PPKs for the production of NTPs [22,52]. The excess of polyP should prevent depletion of sufficiently long polyP chains since acceptance of very short chains (n < 10) might differ between different PPKs [10,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been successfully used before as one-pot reactions to produce different types of nucleotides from their corresponding nucleobase and sugars. [69][70][71][72][73] Both, RK and RPPK, use ATP for the phosphorylation reactions. Different regeneration systems have been used for the rephosphorylation of ADP (RK reaction) or AMP (RPPK reaction).…”
Section: Polyp-based Production Of Atp From Adeninementioning
confidence: 99%